A Study of Serum Iron Profile in Patients with Chronic Kidney Disease - Shastry, Indira; Belurkar, Sushma (Annals of Pathology and Laboratory Medicine, 2020)
Background: Even though anemia and iron deficiency can increase the morbidity and mortality in patients with chronic kidney disease (CKD), an iron overload can be dangerous as well. Aim: Identify the number of CKD patients with iron deficiency, iron overload, acute phase reaction and anemia of chronic disease in a tertiary care hospital. Material and methods: The study was conducted in Kasturba medical college, Manipal. 154 patients with CKD were selected for the study irrespective of their treatment status with hematinics and/or erythropoietin. Results: The mean total serum iron levels were 61Î¼g/dl, Total Iron Binding Capacity (TIBC) 216.43 Î¼g/dl, serum ferritin 539.68 Î¼g/dl, and transferrin saturation of 32.18% respectively. When the serum iron profile of individuals was analyzed, majority (54.25%) of the patients were found to have acute phase reaction and most of them were in advanced stage of renal failure. Normal serum iron profile was found in 37.2% patients, iron overload in 2.2%, anemia of chronic disease in 5.3% and iron deficiency in 1% cases. These findings were statistically significant with the P value of 0.001. Conclusion: Most common type of serum iron profile found in the study population was acute phase reaction (54%) and majority of them were in stage 5 renal failure. Hence, before beginning an iron therapy, all the patients with anemia in chronic kidney disease should be evaluated for body iron status to prevent iron overload.